Canadian Science Meets Parliament: Building relationships between scientists and policymakers. (20th January 2021) - Zhao, Jiaying; Azad, Meghan B; Bertrand, Erin M; Burton, Cole; Crooks, Valorie A; Dawson, Jackie; Ford, Adam T; Kaida, Angela; Krishnaswamy, Arjun; Kuok, Chikin; Mah, Catherine L; McTaggart, Matt; et al.
Abstract: The first Science Meets Parliament event in Canada was held in November 2018 in Ottawa, where twenty-eight Tier II Canada Research Chairs (a specific class of Canadian university professor acknowledged by their peers as having the potential to lead in their field) from diverse disciplines met with forty-three Members of Canadian Parliament and Senators. The main goal of this event was to facilitate communication between these two key pillars of the society, to promote mutual understanding of the nature of their respective work, roles, and responsibilities, and to build long-term relationships. Here, we, representatives of the first cohort of scientists to participate in the program, summarize our experiences and lessons learned from this event, as well as our assessment of the benefits of attending this event for scientists, policy decision-makers, and institutions. Furthermore, we provide suggestions for similar future events in Canada and elsewhere.